Dermatofibrosarcoma protuberans of head and neck: Clinical outcome of nine cases treated with imatinib - Lakhan Kashyap; Vanita Noronha; Vijay Patil; Amit Joshi; Abhishek Mahajan; Neha Mittal; Kumar Prabhash (Cancer Research, Statistics, and Treatment, 2019)
Background: Dermatofibrosarcoma protuberans (DFSP) of head and neck is rare and presents a unique challenge as surgery may be associated with poor cosmetic and functional outcomes or inadequate surgical margins. There is a paucity of data regarding the use and effectiveness of imatinib in head and neck DFSP. We retrospectively analyzed head and neck DFSP cases treated with imatinib. Patients and Methods: Data of nine head and neck DFSP cases treated with imatinib were retrieved from our hospital electronic medical records. Demographic and toxicity data were presented using descriptive statistics and simple percentages; survival was calculated using the Kaplan–Meier method. Results: The median age was 40 years (range, 22–47 years) with almost equal male to female distribution. The site of primary tumor was scalp in seven patients, face and neck in one patient each. One-third of the patients had metastatic disease; sites of metastases included lung, lymph node, soft tissue, and brain. Fibrosarcomatous variant was present in four patients. Eight patients underwent wide local excision for the primary tumor. Three patients each received imatinib in the neoadjuvant, adjuvant, and palliative setting. The response rate to imatinib in the neoadjuvant and palliative setting was 66.7% and 33.3%, respectively. Four patients received adjuvant radiotherapy (RT) after surgery for recurrent disease and one patient received palliative hemostatic RT to the local site. The median duration of follow-up was 84 months (range, 2–148 months), and median recurrence free survival was 82 months (interquartile range, 74–83 months). All patients were alive until last follow-up. Conclusions: Head and neck DFSP requires multimodality management with incorporation of neoadjuvant imatinib and adjuvant RT to achieve favorable clinical outcomes.